Zastosowanie telematyki i systemów telematycznych w sferze bezpieczeństwa sanitarnego - Janik, Marcin; Zacharko, Lidia (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
Effective state’s functioning in the field of sanitary security depends on the correct activity of public administration. Hence, there exists a necessity to create adequate systems and activity procedures which, on the basis of the possessed data resources and carried out analysis, will be able to pick up the incidents being in the area of interest of an epidemiologic authority.
Keywords: sanitary security; telematics; telematic systems